Translational Shifts of Syntactic and Lexical Markers of Ideology: Reporting the Iraqi Conflict in Polish Reprint Press - Gumul, Ewa (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2011)
The present paper focuses on the notion of mediating source-text ideology in press translation, investigating lexico-grammatical resources. This study is partly set within the framework of Critical Discourse Analysis. The analysis focuses on such features as disambiguation or creation of grammatical metaphors (i.e., nominalisation and denominalisation), changes in transitivity patterns, modifications of the levels of modality, as well as shifts in lexical choice, semantic prosody and cohesion patterns. The source of the texts analysed in this paper is a Polish reprint magazine, Forum, publishing translated articles from a variety of English-language quality press titles. The articles selected for the analysis deal with the Iraqi conflict in 2003 and its aftermath. The aim of the study is to ascertain whether the lexical choice and the syntactic structures employed in the target texts engender changes in the ideological content of the source texts and the projected point of view. Given the nature of reprint press, a hypothesis has been formulated that the source-text ideology might remain unchanged in the process of translation or the translator’s intervention is expected to be minimal. The results reveal, however, that a substantial proportion of the translated texts fall within the category of partial mediation, projecting an altered point of view to a target-text audience.